Ethical and Practical Considerations arising from Community Consultation on Implementing Controlled Human Infection Studies using Schistosoma Mansoni in Uganda - Egesa, Moses; Ssali, Agnes; Tumwesige, Edward; Kizza, Moses; Driciru, Emmanuella; Luboga, Fiona; Roestenberg, Meta; Seeley, Janet; Elliott, Alison M. (Global Bioethics, 2022)
Issues related to controlled human infection studies using Schistosoma mansoni (CHI-S) were explored to ensure the ethical and voluntary participation of potential CHI-S volunteers in an endemic setting in Uganda. We invited volunteers from a fishing community and a tertiary education community to guide the development of informed consent procedures. Consultative group discussions were held to modify educational materials on schistosomiasis, vaccines and the CHI-S model and similar discussions were held with a test group. With both groups, a mock consent process was conducted. Fourteen in-depth key informant interviews and three group discussions were held to explore perceptions towards participating in a CHI-S. Most of the participants had not heard of the CHI-S. Willingness to take part depended on understanding the study procedures and the consenting process. Close social networks were key in deciding to take part. The worry of adverse effects was cited as a possible hindrance to taking part. Volunteer time compensation was unclear for a CHI-S. Potential volunteers in these communities are willing to take part in a CHI-S. Community engagement is needed to build trust and time must be taken to share study procedures and ensure understanding of key messages.
Keywords: Endemic; Controlled human infection; Informed consent